Family-friendly and human-capital-based immigration policy - Harriet Duleep; Mark Regets (IZA World of Labor, 2017)
Immigrants who start with low earnings, such as family-based immigrants, experience higher earnings growth than immigrants who are recruited for specific jobs (employment-based immigrants). This occurs because family-based immigrants with lower initial earnings invest in human capital at higher rates than natives or employment-based immigrants. Therefore, immigrants who start at low initial earnings invest in new human capital that allows them to respond to the ever-changing needs of the host country's economy.
Keywords: J6; J24; 330; immigrant selection; immigration policy; earnings growth; human capital investment